The psychological impact of self-recording on recording on reducing speech anxiety and building confidence - Nizomova, Zuxra Baxriddin qizi; Sulaymonova, Madina Amrullo qizi (The Lingua Spectrum, 2026)
Self-recording stands out as a powerful psychological tool for language learners battling speech anxiety. By creating a private, controlled practice space, it dismantles the fear typically tied to public performance. Learners gradually habituate to hearing their own voice, transforming their inner critic into a constructive mentor rather than a harsh judge. This method significantly reduces cognitive load during real-time conversations. When students record themselves, they can focus on delivery without the pressure of immediate social evaluation. Errors shift from embarrassing failures to valuable data points for targeted improvement, fostering a growth mindset. Research consistently shows that reflective self-recording builds learner autonomy. Students gain ownership of their progress, analyzing patterns in their speech at their own pace. This independence proves crucial for sustainable skill development across diverse linguistic contexts. Ultimately, regular self-recording cultivates emotional resilience. It equips learners with confidence that extends beyond the classroom, ensuring lasting motivation and robust speaking proficiency throughout their language journey.